Analyzing the Alignments of Roads by Giving Weightages to Various Factors - a Case Study - Peerzade, Syed Ghouse Mohiuddin N; Patil, Dhananjay S. (International Journal of Data Science, 2022)
there is an increasing demand of Infrastructure roads due to increase in road traffic and related issues in safety. Roads are the dominant mode of transportation in India. Roads carry almost 85 percent of the country’s passenger traffic and more than 62 percent of its freight traffic Due to improvement in transportation network, reduction in transportation costs, such as reduction in travel time, decrease in vehicle operations cost, increased safety and reduction in the level of air and noise pollution. In addition to reduction is transportation cost, it also increases comfort to passenger and enhancing land value. Widening of road is mostly the case followed for the increasing demand. However, nowadays, for catering the needs of increasing traffic demand, Greenfield alignment is also as an option. Hence, there are advantages and disadvantages in both the alignments. This study involves for comparing and analyzing a NH 160A highway section between Ghoti to Trimbakeshwar for a length of 14.3 km. This paper compares the pros and cons of both alignments, costing of both the alignments, Geometry of both alignments; problems/issues like encroachment, forest area, Utilities in both alignments. In this study, the optimal alignment has been arrived by bringing all the issues to a common platform with a grading system. Further, different scenarios considered based on the requirement of a Client by doing Sensitivity analysis for various cases.